2016
DOI: 10.1186/s41110-016-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte zinc and serum copper in male and female adolescents according to puberty stage at different growth phases

Abstract: Background Considering that modification in body composition and growth velocity leads to alterations in zinc and copper nutritional status, the purpose of the study was to assess erythrocyte zinc and serum copper in adolescents of both genders, according to the stage of sexual maturity at different growth phases. Methods Two hundred and eighty-six adolescents were assessed, 157 were female, with body mass index Z-score between −2 and +2. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
2
0
0
Order By: Relevance
“…However, the serum concentration of copper was negatively correlated with the free zinc concentration (supplemental Table S1). As shown in supplemental Table S2, no difference between males and females has been observed for the serum concentrations of manganese, iron or selenium, but for copper a significantly higher concentration has been found in the sera from females (19.83 ± 0.64 nM) than in those from males (16.63 ± 0.23 nM), which is in line with previous reports [34,35]. The homeostases of zinc and copper are connected with regard to resorption and transport in the serum.…”
Section: Resultssupporting
confidence: 91%
“…However, the serum concentration of copper was negatively correlated with the free zinc concentration (supplemental Table S1). As shown in supplemental Table S2, no difference between males and females has been observed for the serum concentrations of manganese, iron or selenium, but for copper a significantly higher concentration has been found in the sera from females (19.83 ± 0.64 nM) than in those from males (16.63 ± 0.23 nM), which is in line with previous reports [34,35]. The homeostases of zinc and copper are connected with regard to resorption and transport in the serum.…”
Section: Resultssupporting
confidence: 91%
“…Also, a decrease (not statistically significant) in zinc levels was observed in male group compared with female group which is in conformity with previous reports where it was shown that higher concentrations of zinc was seen in females than in males [26,27]. Zinc level is influenced by modifications that occur at different stages of puberty in males and it is directly influenced by gender variations [28]. Zinc, copper and magnesium showed positive significant correlations in the malaria subjects which do not agree with a previous finding that zinc and copper compete with each other as antagonist in order to properly regulate the physiological pathways in the body [29].…”
Section: Discussionsupporting
confidence: 90%